Penerapan Metode HIRADC pada Bagian Proses Penerimaan di PT. CA - Hidayat, Dian Friana; Hardono, Joko (Journal Industrial Manufacturing, 2021)
Every job has the opportunity of the risk because occurrence of work accidents can be caused by various factors. PT. CA is a large distributor of motorcycle spare parts which has activities including receiving goods from fabrication and then storing them in temporary warehouses before being distributed to dealers in various regions. The company's activities have a large potential for accidents due to several operations. To hazard identification, risk assessment, and determining control in any work that occurs or has the potential to occur, it is necessary to analyze using HIRADC. The method used is a descriptive method described in the flow process and then identified possible hazards that occur in each activity step. After the identification process is complete, a risk assessment is carried out to determine the form of control. The object of research is the receiving section of the work area. The results of this study are that the receiving section has 7 existing activities and there are 20 potential hazards that are possible, from these potentials the current control is to maximize APD to minimize danger. The highest level of risk is substantial in the activity of moving cargo to temporary storage or inspection areas with a potential danger of crashing into workers which has an impact on limb injuries, fractures, and even death, so this activity is a concern to avoid work accidents. In addition, it is determined that hazard control is carried out by means of forklift lanes that are not allowed to be passed by workers and control recommendations are in the form of setting SOPs, ensuring that forklifts complete their activities to carry out inspections. Keywords: Occupational safety, potential hazard, identification, risk, control, HIRADC